The plight of the diasporic Muslim community in the West - Abdul Razak, Mohd Abbas; Salah, Machouche (Mission Soft Foundation, 2022)
Etymologically diaspora comes from a Greek word which means scattered and dispersed. Generally, a diasporic community explains people who have to leave their homeland for another part, region or country of the world. In most instances, the act of leaving one’s motherland is involuntary. Many diasporic communities around the globe are forced to leave due to unfavourable conditions in their place of origin or driven away by an invading army or regime. For a very long time, Western media uses the word diaspora exclusively to describe the Jewish diaspora alone, but in actual fact, there are many others that be classified as diasporic communities. A few examples to state here will be the Hijrah made by the Prophet of Islam and his followers, three million Muslims who were expelled from Spain between the years 1492-1610, Africans who were taken away to the Americas under the slave trade (1776-1865), the Palestinians who have to leave their country due to the Israeli occupation and atrocities, Rohingyas due to the genocide carried out by the regime in Myanmar, and very recently, the exodus and migration of 6.8 million Syrian refugees have to flee for their safety and security. It is said that about 1 million Syrians crossed over to Europe as refugees and asylum seekers.